A ética sob a ótica da poética candanga - Souza, Ildefonso Pereira de (2013)
The present study investigates whether the thematic related to principles and ethical-moral values appears as a recurrent theme in the production of the candangos poets (born in Brasilia or fond of it), whereas their compositions show "grace," "beauty" and "truth" - elements, a priori, inseparable from the poetic. The research aims to point out, whether the authors and their poems act in the sense of generate a universe of reflection which proves itself capable of shaping consciences; in a way that people become sensitive to realize that the highest of the ethical principles is the one that stands up for life in all its fullness for all (John 10: 10), according to what Jesus himself wants. And also as Don Bosco dreamed, when he metaphorized that Brasília would be a land where "milk and honey" would flow. To this competence of the authors analyzed, is given the name of ethical-moral poetic", for effect of conclusion of this work.